(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian economy is distinguished by the complex combination of agricultural, manufacturing and service economic activities. Alternatively, the Indian economy may be narrowly categorized into major industries, including the main, secondary and tertiary sectors, most generally referred to as the agriculture, manufacturing and services sectors. A paradigm change in Indian economy was observed with the introduction, in 1995, of the New Economic Strategy, which diluted the model of mixed economy and opened up India’s economy. The pace of economic growth was accompanied by economic liberalization initiatives, including corporate reform, privatization of state-owned companies and decreased external trading and investment restrictions. The goal of this research analysis is to examine and compares data concerning the contributions in the country’s total GDP from the key sectors of Indian economies (i.e. agriculture, industry and services) during 1995-96 to 2014 - 15. GDP details from secondary sources have been extracted (Open Government Data Platform India). Furthermore, statistical methods and analyses such as correlation analysis, variance analysis and F-tests were used to draw useful conclusions from the available secondary data.The analysis concludes that the output of the major sectors in the 1990-91 to 2009-10 era in terms of GDP contribution is important. The rising share of the service sector in the country’s total GDP suggests that we are a developed nation that is struggling to expand. All developing economies worldwide have ample share in their respective GDPs in the service sector, so if our country is still moving in the same direction, there is no damage. The main challenge in our economy is that industry’s GDP projections and business employment have a substantial difference.